2022
DOI: 10.3390/ijerph192316122
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Coping and Considerations of Leaving the Profession—A Cross-Sectional Online Survey of Teachers and School Principals after Two Years of the Pandemic

Abstract: Teaching is amongst the six professions with the highest stress levels and lowest job satisfaction, leading to a high turnover rate and teacher shortages. During the pandemic, teachers and school principals were confronted with new regulations and teaching methods. This study aims to examine post-pandemic stress levels, as well as resilience factors to proactively cope with stress and thoughts of leaving the profession among teachers and school principals. We used a cross-sectional online survey. The validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(59 reference statements)
0
4
0
1
Order By: Relevance
“…The pandemic brought unrealistic and unexpected changes in the school's work environment where all classroom teaching and other activities shifted to completely online mode. These sudden changes led to increase in teacher anxiety, stress and burnout due to role ambiguity, role conflict and minimal support from the school district administration [62,[96][97][98], and psychosomatic health problems due to psychosocial demand factors (job insecurity, workload, lack of organizational justice) and lack of social support [99]. Teacher's had to manage conflicts and stress arising from Conflicts in PK-12 Schools: Causes, Consequences and Management DOI: http://dx.doi.org/10.5772/intechopen.1004344 environmental, (school administration, student's home environment and parentteacher relationship), role related (climate and classroom management, virtual teaching, and student issues), and personal factors (work-family balance, uncertainty and work over load) as reported in a study by Boneh et al [100].…”
Section: Teacher Conflict and Stress During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic brought unrealistic and unexpected changes in the school's work environment where all classroom teaching and other activities shifted to completely online mode. These sudden changes led to increase in teacher anxiety, stress and burnout due to role ambiguity, role conflict and minimal support from the school district administration [62,[96][97][98], and psychosomatic health problems due to psychosocial demand factors (job insecurity, workload, lack of organizational justice) and lack of social support [99]. Teacher's had to manage conflicts and stress arising from Conflicts in PK-12 Schools: Causes, Consequences and Management DOI: http://dx.doi.org/10.5772/intechopen.1004344 environmental, (school administration, student's home environment and parentteacher relationship), role related (climate and classroom management, virtual teaching, and student issues), and personal factors (work-family balance, uncertainty and work over load) as reported in a study by Boneh et al [100].…”
Section: Teacher Conflict and Stress During Covid-19mentioning
confidence: 99%
“…The results showed that lower scores on self-efficacy related to instructional strategies led to higher burnout scores [112]. A study conducted by Lucker et al [96] explored the sources of support that teachers felt were important to them. The teachers indicated in their survey responses that family, friends, pupil's student's parents, school management, coworkers were the most important individuals who supported them during the pandemic.…”
Section: Teacher Coping and Conflict Management During Covid-19mentioning
confidence: 99%
“…Des études antérieures et plus récentes ont démontré qu'en temps de crise en milieu scolaire, les routines organisationnelles, les pratiques de gestion et la santé des acteurs sont durement touchées (Lemieux et al, 2021;Lücker et al, 2022;Mutch, 2015;Netolicky, 2020;Smith et Riley, 2012). Les élèves se tournent vers les adultes, notamment les directions d'école, pour des conseils rassurants (Mutch, 2015).…”
Section: Problématique Contexte Et Objectifs De La Rechercheunclassified
“…Workload and work-related stress have been cited as key reasons for leaving the profession [ 16 , 23 ] and between 2020 and 2022 there was an 82% increase in all teaching staff leaving the profession in Wales [ 24 ]. Furthermore, evidence suggests gender differences exist in perceptions of stress and exhaustion, with female school leaders exhibiting higher perceived stress [ 25 ] and symptoms of exhaustion and fatigue compared to their male counterparts [ 26 ]; further research is required to examine this in the context of COVID-19.…”
Section: Introductionmentioning
confidence: 99%